Enrofloxacin assay validation and pharmacokinetics following a single oral dose in chickens - Da Silva, R. G.; Reyes, F. G. R.; Sartori, José Roberto [UNESP]; Rath, S. (Blackwell Publishing, 2006)
The pharmacokinetics of enrofloxacin (ENRO), a fluoroquinolone antimicrobial agent, was studied in male broiler chickens (Cobb) after single oral administration of 10 mg of ENRO/kg b.w. A high-performance liquid chromatography-photodiode array detector (DAD) (HPLC-DAD) method was developed and validated and used for quantitation of ENRO and its major metabolite ciprofloxacin in plasma. The HPLC analyses were carried out using a cationic-octadecyl mixed column and 0.05 mol/L phosphate buffer (pH 2.5)/acetonitrile as mobile phase. The sample preparation of plasma consisted of the precipitation of proteins followed by solid phase extraction on cationic-octadecyl mixed cartridges. The method was validated considering linear range, linearity, selectivity, sensitivity, limit of detection (LOD), limit of quantitation (LOQ), intra- and inter-day precisions and accuracy. The LOD and LOQ for both fluoroquinolones were 60 and 200 ng/mL for plasma. The plasma concentration vs. time graph was characteristic of a two-compartment open model. The maximal plasma concentration of 1.5 +/- 0.2 mg/mL was achieved at 9 +/- 2 h. The elimination half-life and the mean residence time of ENRO were 1.5 +/- 0.2 and 15.64 h, respectively. The area under the concentration-time curve was calculated as 35 +/- 4 mg(.)h/mL.